Using Elastic Properties as a Predictive Tool to Identify Pore-Fluid Type in Carbonate Formations - Jasim Al-Khafaji, Mahmoud; Mustafa Al-Kattan, Wafaa’ (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
The aim of this study is for testing the applicability of Ramamoorthy and Murphy method for identification of predominant pore fluid type, in Middle Eastern carbonate reservoir, by analyzing the dynamic elastic properties derived from the sonic log. and involving the results of Souder, for testing the same method in chalk reservoir in the North Sea region. Mishrif formation in Garraf oilfield in southern Iraq was handled in this study, utilizing a slightly-deviated well data, these data include open-hole full-set logs, where, the sonic log composed of shear and compression modes, and geologic description to check the results. The Geolog software is used to make the conventional interpretation of porosity, lithology, and saturation. Also, include PVT and water analyses as inputs in Batzle and Wang correlations in order to calculate mechanical properties of oil and water at reservoir conditions. The shear velocity and density logs are used to calculate the shear modulus (G), for each (0.1254) meter.  The dry frame bulk modulus correlation of the original method was not followed, instead, a new dry frame bulk modulus correlation of Saxena is used to avoid the uncertainty in the porosity type exist in the formation which needs special core description. Then, Gassmann’s equations were used to determine the bulk moduli of the rock assuming two saturation conditions; the first is 100% water saturated, and the second is 100% oil saturated.  Using elastic properties equations of Love’s, and the resulted bulk moduli, two corresponding ∆t(s), (for oil and for water), were computed for each depth level. Then these ∆t(s) were plotted with sonic ∆t in the same track, and compiled with the conventional log interpretation, to compare the results. The method was a good indicator of the fluid type in the high porosity zones, unlike for the tight or clay-rich zones. The results are very conformable to the conventional interpretation, the OWC in both model and conventional interpretation are so close with error percentage of (0.03%).